Transport of polystyrene nanoplastics in natural soils: Effect of soil properties, ionic strength and cation type - Wu, Xiaoli; Lyu, Xueyan; Li, Zhengyu; Gao, Bin; Zeng, Xiankui; Wu, Jichun; Sun, Yuanyuan (The Science of the total environment, 2020)
Nanoplastics as emerging pollutants have caused growing concerns and posed potential threats to the environment. Nonetheless, only few studies investigated transport behaviors of nanoplastics in natural soils. In this study, column experiments were conducted to investigate the effect of soil properties, ionic strength and cation type on the transport of polystyrene nanoplastics (PSNPs) in a desert soil (DS), a black soil (BS) and a red soil (RS). The effluent recovery of PSNPs in three soils followed the order of DS (0%–96.8%) > BS (0%–87.5%) > RS (0%). The retention of PSNPs was positively correlated with Fe/Al oxides contents (DS: Fe-2.69%, Al-12.6%; BS: Fe-4.04%, Al-15.9%; RS: Fe-6.57%, Al-26.9%), whereas negatively correlated with soil pH (DS: 9.75; BS: 6.57; RS: 4.97). Soil minerals and pH were thus identified as the crucial soil properties determining transport of PSNPs, due to their coupled effects on surface charges to affect electrostatic interactions between soils and PSNPs. In addition, increasing solution ionic strength strongly inhibited the transport of PSNPs in the DS (0%–96.8%) and BS (0%–87.5%). Ca2+ (IS: 1–5 mM) was more pronounced in enhancing PSNP retention than Na+ (IS: 1–20 mM). Our findings highlight that the transport and fate of PSNPs in natural soils are highly sensitive to soil physicochemical properties, ionic strength and cation type, and reveal that nanoplastics have strong mobility ability in soils with high pH and low Fe/Al oxides contents, which may pose potential risks to the soil and groundwater environment. [Display omitted] •PSNPs retention in soils was positively correlated with Fe/Al oxides contents.•PSNPs retention in soils was negatively correlated with soil pH.•PSNPs transport decreased with increasing ionic strength in soils.•Ca2+ was more pronounced in inhibiting PSNPs transport than Na+ in soils.